Sistem Informasi Manajemen dalam Evaluasi Pembelajaran di SMK Sinar Husni Helvetia - Melati Br. Lubis; Rustam Rustam (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to examine the implementation of Management Information Systems (MIS) in the evaluation of learning at SMK Sinar Husni Helvetia, particularly in the areas of information collection, data analysis, and dissemination through online applications such as Google Forms, Quizizz, Wordwall, and Google Classroom. The research uses a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results indicate that MIS supports teachers in designing, distributing, and analyzing evaluation data efficiently and effectively. The use of online applications allows learning assessments to be more practical, interactive, and to provide immediate feedback. This system contributes to more structured teaching and learning activities, enabling schools to achieve educational goals more effectively. The study also highlights the importance of integrating technology with ethical and religious values in developing digital-based educational information systems.